Dicyma pulvinata isolates colonizing Microcyclus ulei stromata in rubber - Mello, Sueli Corrêa Marques de; Santos, Maria de Fátima; Silva, João Batista Tavares da (Pesquisa Agropecuaria Brasileira, 2006)
Dicyma pulvinata is an efficient biocontrol agent of Microcyclus ulei, causal agent of South American leaf blight. The objective of this work was to obtain strongly antagonistic isolates. A survey was carried out in rubber plantations located in 14 municipalities in the Sates of Acre, Amazonas, Bahia, Mato Grosso, Pará and Roraima, Brazil, obtaining 52 isolates of D. pulvinata. The antagonistic fungus was isolated on potato-dextrose-agar (PDA) plates and identified based on morphological characteristics of conidiophores and conidia, and colony appearance. The antagonic effect was tested by inoculating D. pulvinata on Fusicladium macrosporum lesions induced on rubber plants, previously. In order to maintain the morphological and pathogenic traits, fungus isolates were preserved by lyophilization, deep freeze (-80oC) and cryogeny. All isolates were introduced into Embrapa Recursos Genéticos e Biotecnologia fungus collection.